The Impact of Pre- and Postarrival Mechanisms on Self-rated Health and Life Satisfaction Among Refugees in Germany - Ambrosetti, Elena; Dietrich, Hans; Kosyakova, Yuliya; Patzina, Alexander (Frontiers in Sociology, 2021)
In this study, we focus on the evolution of refugees’ well-being in the first years after their arrival in Germany. In contrast to other immigrants (e.g., labor migrants), refugees experience higher risks of unexpected and traumatic events and insecurity before and during their migration and face various legal and structural barriers in the receiving country. We contribute to the existing literature by exploring from a dynamic perspective possible pre- and postarrival determinants of refugees’ life satisfaction and self-rated health upon arrival in Germany and the development of their life satisfaction and self-rated health in the process of becoming established. Applying linear regression and panel models with recent longitudinal data from the IAB-BAMF-SOEP Survey of Refugees in Germany, we find significant effects of prearrival factors, such as traumatic experiences and the complexity of migration, on both life satisfaction and self-rated health at the time of the first interview. Regarding postarrival factors, our results suggest that improvement in language proficiency and labor market status significantly shape refugees’ life satisfaction and self-rated health. The time-dynamic analyses reveal substantial improvements in life satisfaction upon the approval of refugee status and the transition from shared housing to private accommodations. However, we find no improvements in self-rated health due to legal status but rather deterioration effects due to long-term residence in shared housing.